Genetic Screening of Deficiency of Uridine Monophosphate Synthase in Holstein Freisian Crossbred Cattle - Ignetious, Sherly; Joshi, Shrikant; Aich, Ranjit; Macwan, Shefali (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
Fifty Holstein Friesian (H.F) crossbredcattle were screened for Deficiency of Uridine Monophosphate Synthase (DUMPS) using PCR-RFLP. Blood samples were collected from jugular veins in 2 ml capacity vaccutainers containing 2 mg/ml (K2 EDTA). DNA was isolated from the blood samples by using whole blood extraction kit. PCR was performed for amplification of polymorphic region of Uridine Monophosphate Synthase (UMPS) gene (108 bp) on bovine chromosome 1. The PCR products of 108 bp were digested with AvaI endonuclease enzyme. The normal allele in unaffected cattle produced three fragments of 53 bp, 36 bp and 19 bp. No animal was found carrier for UMPS gene. The genotype frequency of normal individuals and the gene frequency of normal allele were found to be one.